Pre-treatment amygdala activation and habituation predict symptom change in post-traumatic stress disorder - Hinojosa, Cecilia A.; VanElzakker, Michael B.; Kaur, Navneet; Felicione, Julia M.; Charney, Meredith E.; Bui, Eric; Marques, Luana; Summergrad, Paul; Rauch, Scott L.; Simon, Naomi M.; Shin, Lisa M. (Frontiers in Behavioral Neuroscience, 2023)
Trauma-focused psychotherapy approaches are the first-line treatment option for posttraumatic stress disorder (PTSD); however, up to a third of patients remain symptomatic after treatment completion. Predicting which patients will respond to a given treatment option would support personalized treatments and improve the efficiency of healthcare systems. Although previous neuroimaging studies have examined possible pre-treatment predictors of response to treatment, the findings have been somewhat inconsistent, and none have examined habituation to stimuli as a predictor. In the current study, 16 treatment-seeking adults (MAge=43.63, n=10 female) with a primary diagnosis of PTSD passively viewed pictures of emotional facial expressions during functional magnetic resonance imaging (fMRI). After scanning, participants rated facial expressions on both valence and arousal. Participants then completed 8 weekly sessions of prolonged exposure (PE) therapy. PTSD symptom severity was measured before and after treatment. Overall, participants showed symptomatic improvement with PE. Consistent with hypotheses, lesser activation in the amygdala and greater activation in the ventromedial prefrontal cortex during the presentation of fearful versus happy facial expressions, as well as greater decline in amygdala activation across blocks of fearful facial expressions at baseline, were associated with greater PTSD symptom reduction. Given that the repeated presentation of emotional material underlies PE, changes in brain responses with repeated stimulus presentations warrant further study as potential predictors of response to exposure therapies.